Effects of feeding earthworm or vermicompost on early life performance of broilers under challenging dietary conditions - Gürbüz Daş; John M. Brameld; Tim Parr; Mohammad M. Seyedalmoosavi; Solvig Görs; Cornelia C. Metges (Poultry Science)
ABSTRACT: We investigated if feeding earthworms (EW) or vermicompost (VC) to broilers improves performance and aids in coping with dietary challenges from a soluble non-starch polysaccharide (NSP)-enriched diet (negative control diet; CON-). Newly-hatched male Cobb-500 birds (N = 480) were fed either a positive (+) control diet (CON+, n = 240) or CON+ supplemented with either 1% EW (CON+EW; n = 120) or 1% VC in DM (CON+VC; n = 120) for 8 d (Period 1; P1). At the end of P1, blood and intestinal samples were taken from half the birds in each group. Half of remaining birds on CON+ stayed on CON+ for further 8 d (P2; d9–16) or switched to CON-. Birds on CON+EW and CON+VC in P1 were switched to CON- in P2 (CON-EW and CON-VC, respectively). The CON+VC improved (P < 0.05) BW and ADG in P1 through an elevated feed intake (FI) (P < 0.05) with no effect on FCR. CON+EW did not differ from the CON+ in terms of growth and FI in P1. In P2 CON- did not affect growth or DMI relative to CON+. In the end of P2, 10% of CON+ birds had pasty vent (PV). CON- increased incidence of PV and CON-VC aggravated this effect (P < 0.05), whereas CON-EW did not differ from CON+. CON- diet reduced proportion of 16S rDNA in colon digesta (P = 0.049), while CON-EW and CON-VC did not differ from CON+. Compared to CON-, CON-EW tended to decrease (P = 0.072) incidence of PV. Ceca were heavier (P < 0.05) in CON-EW than in CON+ fed birds. In conclusion, the challenge diet induced PV and reduced bacterial 16S rDNA in colon digesta, likely due to soluble NSP-induced anti-nutritive effects. VC supplementation enhanced early growth by increasing feed intake. Provision of EW did not impact performance but decreased incidence of PV and increased cecal size, suggesting that potential inoculation with beneficial microorganisms may counteract NSP effects.